Development of Agroforestry to Support Food Security of Farmers in Bangko Hamlet, West Halmahera - Tamrin, Mahdi; Kamaluddin, Abdul Kadir; B., Sabaruddin (TECHNO: JURNAL PENELITIAN, 2025)
Good forest management practices will certainly have an impact on the economic condition of the community around the forest. One form developed in Indonesia is the agroforestry pattern. Agroforestry is a form of land management system that functions to increase productivity and species diversity, so it is often used as an example of a sustainable land management system. This research aims to obtain information on the types of plants that have been planted to determine the potential for the development of agroforestry systems in an effort to improve the economic and ecological functions of the land. The research modality with a field observation approach is direct observation and careful recording of the studied study of the agroforestry system developed. The results of the study show that the development of agroforestry in Bangko Hamlet, West Halmahera with an alley cropping system. Farmers take advantage of the space under the stand by planting various types of agricultural crops with high economic value for sale or household consumption. This can be seen from the crop patterns used by farmers and the production products produced. There are several types of forest and agricultural plants, including white teak, motoa, linggua and types of agricultural plants, namely cassava, bananas, dragon fruit and mangoes.